Musical Intangible Cultural Heritage of the Polissian Region Near Rivne: Status and Study - Rybak, Yuriy (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
The folkloric tradition of the Polissian region near Rivne is archaic, colourful, and comparatively intact into the present. Research in the area has been conducted since the early days of ethnographic studies over two hundred years ago, though the results of such studies are far from sufficient. Three locally specific phenomena which require priority safeguarding and focused research are: the ritual of “visitations with the Kust” (водіння Куста, vodinnia Kusta); the turned wooden flute (дудка-викрутка, dudka-vykrutka); and solo singing (солоспів, solospiv). I provide a general description of these three cultural elements and scholarly research about them. Two of these elements have been added to the National Register, however this sometimes gives specialists and leaders in the cultural sphere an impression that they can now reduce the intensity of work. An appropriately comprehensive knowledge of the element can only be achieved through continued dedicated field expeditions, scholarly articles, and conferences.